Produção de ácido sulfúrico a partir da oxidação hidrotérmica da pirita presente no carvão mineral proveniente da jazida de Candiota-RS - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Currently due to the increase in crude oil and gas prices, and also the scarcity of these resources, energy production industries around the world seek to accelerate the development of the mineral coal industry, whose application is reduced to energy generation through of its direct combustion. With this, there is concern about the emission of pollutants released in this thermal process, such as sulfur compounds, mainly sulfur dioxide (SO2) and sulfur trioxide (SO3), from the pyritic sulfur contained in coal, in addition to nitrogen compounds (NOX) and greenhouse gases. Mineral coal with low sulfur content has been extinguished, and as a result, technologies have been developed to desulphurize coal with medium or high sulfur content, removing pyritic and organic sulfur for its industrial use in the production of other products, such as sulfuric acid, as a way to add value to the material. In this sense, the aim of this work is the production of sulfuric acid through hydrothermal oxidation technology under pressure of pyrite present in mineral coal. The experiments were carried out at the Energy and Carbochemical Laboratory (LEC), located at Federal University of Pampa, Bagé/RS, using mineral coal from the deposit located at the city of Candiota-RS. Initially, the mineral coal was submitted to characterization by immediate analysis, to determine the ash, volatile, moisture and fixed carbon content, granulometric assay, FT-IR spectroscopy, to determine the presence of minerals and substances present on the surface of the material, and atomic absorption spectroscopy, used to obtain the amount of sulfur indirectly by quantifying the iron present in coal. Then, a solution containing the coal, deionized water and oxygen was added to a Parr reactor, where the reaction of hydrothermal oxidation of the pyrite present in the mineral coal occurred. After 4 h, a pitch was formed and then filtered and separated into a liquid phase, which neutralized with sodium hydroxide (NaOH) 0,025 M, to quantify the amount of sulfuric acid present. The flame mode atomic absorption spectroscopy was used to determine the amount of pyritic sulfur in the reaction liquid product. The solid phase (mineral coal cake) was submitted to acid digestion with concentrated nitric acid (HNO3) and analyzed through flame mode atomic absorption spectroscopy analysis to quantify the remaining pyrite sulfur in the cake. Mineral coal presented moisture content, ash, volatiles and fixed carbon of 10%, 53.11%, 19.68% and 27.21%, respectively. Presenting an average diameter of 330 µm and a pyrite peak (FeS2) in the range of 420 cm-1, the atomic absorption spectroscopy quantified 1.82 % (m/m) of pyritic sulfur in the initial carbon for the process. The sulfur recovery efficiency was 38%, 49.77%, 70% and 86% for the 4 operational conditions studied in this work. The yield of sulfuric acid production using the same conditions was 18%, 36%, 54% and 64.9%. With this, it is concluded that it was possible to recover the pyritic sulfur and produce sulfuric acid through the hydrothermal provision of mineral coal in a satisfactory way in a high-pressure parr reactor.
Keywords: Pirita; Enxofre; Dessulfurização; Espectroscopia; Titrimetria; Pyrite; Sulfur; Desulfurization; Spectroscopy; Titrimetry; ENGENHARIAS